If f ( x ) = 4 x + 2 4 x β , find
f ( 2 0 1 9 1 β ) + f ( 2 0 1 9 2 β ) + f ( 2 0 1 9 3 β ) + β― + f ( 2 0 1 9 2 0 1 8 β ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Given that f ( x ) = 4 x + 2 4 x β , then
f ( x ) + f ( 1 β x ) β = 4 x + 2 4 x β + 4 1 β x + 2 4 1 β x β = 4 x + 2 4 x β + 2 + 4 x 2 β = 1 β MultiplyΒ upΒ andΒ downΒ by 4 x β 2 1 β .
Now we have:
S β = f ( 2 0 1 9 1 β ) + f ( 2 0 1 9 2 β ) + f ( 2 0 1 9 3 β ) + β― + f ( 2 0 1 9 2 0 1 6 β ) + f ( 2 0 1 9 2 0 1 7 β ) + f ( 2 0 1 9 2 0 1 8 β ) = f ( 2 0 1 9 1 β ) + f ( 2 0 1 9 2 β ) + f ( 2 0 1 9 3 β ) + β― + f ( 1 β 2 0 1 9 3 β ) + f ( 1 β 2 0 1 9 2 β ) + f ( 1 β 2 0 1 9 1 β ) = NumberΒ ofΒ 1s = 1 0 0 9 1 + 1 + 1 + β― + 1 β β = 1 0 0 9 β β
This is not a real solution, it's just a way to solve the problem looking to options. See Jahangir and Otto's comments for effective solutions.
For all x it's true that
4 x + 2 4 x β < 1
so must hold also
β i = 1 2 0 1 8 β f ( 2 0 1 9 i β ) < 2 0 1 8 .
Now, we have only two options for the solution, 0 and 1 0 0 9 . But all terms are positive, so only one option is possible: 1 0 0 9 β .
Just to have some New Year's fun, we can write f ( x ) = 2 1 β tanh ( ln 2 ( x β 2 1 β ) ) + 2 1 β . Since tanh t is an odd function and the given points are arranged symmetrically with respect to x = 2 1 β , the answer is 2 0 1 8 Γ 2 1 β = 1 0 0 9 β .
My favorite solution here. Thank you.
Problem Loading...
Note Loading...
Set Loading...
g i v e n
f ( x ) = 4 x + 2 4 x β
f ( 1 β x ) = 4 1 β x + 2 4 1 β x β
= 4 x 4 β + 2 4 x 4 β β
= 4 x 4 + 2 . 4 x β 4 x 4 β β
= 4 x 4 β Γ 4 + 2 . 4 x 4 x β
= 4 + 2 . 4 x 4 β
= 4 x + 2 2 β β
N o w
f ( x ) + f ( 1 β x ) = 4 x + 2 4 x + 2 β = 1 β
1 s t + l a s t = f ( 2 0 1 9 1 β ) + f ( 2 0 1 9 2 0 1 8 β )
= f ( 2 0 1 9 1 β ) + f ( 1 β 2 0 1 9 1 β )
= 1 β΄ f ( x ) + f ( 1 β x ) = 1 β
w e c a n s e e t h a t , s u m o f e v e r y p a i r f r o m g i v e n s e r i e s i s 1 β
S o ,
T o t a l P a i r = 2 0 1 8 Γ· 2
= 1 0 0 9 β
So, The final answer is 1 0 0 9 β